LADY BEETLES OF NEPAL (Coleoptera: Coccinellidae) FROM THE FIELDS AT NEPAL AGRICULTURAL RESEARCH COUNCIL, KHUMALTAR, LALITPUR - K.C. SAJAN; JAROSLAV VETROVEC; RAM CHANDRA GOULI; BISHNU PRASAD NEUPANE (The Bioscan, 2020)
The diversity of lady beetle fauna of Nepal Agricultural Research Council (NARC), Khumaltar, Lalitpur is studied in this paper. All the findings are included except those of the subfamily Coccinellinae which have been included in a separate paper previously. However, Epilachninae (now Epilachnini) is also included here. In this research, except for Coccinellinae, 7 species from 5 subfamilies (Chilocorinae, Epilachninae, Sticholotidinae, Scymninae and Coccidulinae), 5 tribes (Chilocorini, Epilachnini, Sticholotidini, Scymnini and Noviini) and 6 genera (Chilocorus, Henospilachna, Jauravia, Pharoscymnus, Novius and Scymnus) were collected and identified. The identified species were Chilocorus nigritus (Fabricius, 1798), Henosepilachna kathmanduensis Miyatake, 1985, Henosepilachna vigintioctopunctata (Fabricius, 1775), Jauravia quadrinotata Kapur, 1946, Pharoscymnus flexibilis (Mulsant, 1853), Novius cf. pumilus (Weise, 1892) and Scymnus (Pullus) posticalis Sicard, 1913.